2022
DOI: 10.18063/ijb.v8i3.574
|View full text |Cite
|
Sign up to set email alerts
|

Selective Laser Melted Rare Earth Magnesium Alloy with High Corrosion Resistance

Abstract: Magnesium (Mg) degrades too fast in human body, which limits its orthopedic application. Single-phase Mg-based supersaturated solid solution is expected to possess high corrosion resistance. In this work, rare earth scandium (Sc) was used as alloying element to prepare Mg(Sc) solid solution powder by mechanical alloying (MA) and then shaped into implant using selective laser melting (SLM). MA utilizes powerful mechanical force to introduce numerous lattice defects, which promotes the dissolution of Sc in Mg ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…where P is the laser power input (W), v s is the laser scanning speed (mm/s), l hs is the hatch spacing (mm) and l z is the layer thickness (mm). According to the current work (Yu et al 2022;Yang et al 2022;Cacace and Semeraro 2021;Sing et al 2021), the parameters were controlled for the optimisation as follows: the laser power was varied between 200 and 350 W (i.e. 200 W 230 W 260 W 290W 320W and 350W), and the laser scanning speed was selected between 200 and 1600 mm/s (i.e.…”
Section: Materials and Lpbf Processingmentioning
confidence: 99%
“…where P is the laser power input (W), v s is the laser scanning speed (mm/s), l hs is the hatch spacing (mm) and l z is the layer thickness (mm). According to the current work (Yu et al 2022;Yang et al 2022;Cacace and Semeraro 2021;Sing et al 2021), the parameters were controlled for the optimisation as follows: the laser power was varied between 200 and 350 W (i.e. 200 W 230 W 260 W 290W 320W and 350W), and the laser scanning speed was selected between 200 and 1600 mm/s (i.e.…”
Section: Materials and Lpbf Processingmentioning
confidence: 99%
“…Rescanning at a 150% energy density reduced the residual stress by 33.6%; however, the effect on the mechanical properties was detrimental and the sample failed prematurely. Chunyan Zhang et al [22] simulated the temperature field of laser-melting rare-earth magnesium alloy and found that the temperature field showed the characteristics of sudden heating, rapid cooling, and dynamic change. The temperature gradient of the surface was the largest, and the temperature gradient decreased sequentially from the surface to the inside.…”
Section: Introductionmentioning
confidence: 99%